Is bioturbation also reflected on above-ground biogenic sedimentary strutuctures? A hypothesis regarding the estuarine fiddler crab Uca thayeri - Pardo, Juan Carlos Farias [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
We evaluated the vertical distribution of organic matter promoted by construction and maintenance of Uca thayeri biogenic sedimentary structures. By integrating field and laboratory approaches, we estimated the amount of organic matter transported by burrowing activity and chimney building processes. In the laboratory experiment, we used microcosms with different layers of organic matter content: upper (low content/10cm) and lower (high content/10cm). Sediment was physically transported from lower to upper layers in which chimney and burrow profiles reflected organic matter transport after crab activity. In the field experiment, we compared burrow and non-burrow profiles (without visible burrows); chimneys were collected and sediment samples were stratified in the upper (0-4 cm), upper intermediate (4-8 cm), lower intermediate (8-12 cm) and lower layers (12-20 cm), the latter which comprises maximum burrow depth for this species (~20 cm). Burrows had more organic matter than non-burrow layers, acting as traps for sediment and organic compounds. Chimneys showed lower organic matter content when compared to lower burrow layers. Thus, organic matter is disposed (e.g. washed by tides) or consumed (e.g. microbial community) after chimney shaping. The U. thayeri biogenic sedimentary structures affect organic matter vertical distribution of mangrove soils. Lab and field experiments seemed to be complementary for a better understanding of the whole process of organic matter distribution. Ecological implications of above-ground biogenic sedimentary structures are discussed
Keywords: Crustaceo; Caranguejo - Ecologia; Estruturas sedimentares; Crabs